1992
DOI: 10.1093/infdis/165.4.702
|View full text |Cite
|
Sign up to set email alerts
|

Differential Release of Interleukin (IL)-1 , IL-1 , and IL-6 from Normal Human Monocytes Stimulated with a Virulent and an Avirulent Isogenic Variant of Mycobacterium avium-intracellulare Complex

Abstract: Members of the Mycobacterium avium-intracellulare complex (MAC) can exist in a transparent or opaque colonial morphology when cultured on synthetic medium. An opaque variant was developed from a transparent strain of a clinical MAC isolate. Comparison of the two variants showed a greater ability of the transparent colonial variant to infect normal human monocytes as measured by growth in monocyte-bacteria cocultures. Further analyses indicated diminished ability of the transparent variant to induce extracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…In both control and AIDS patients, more IL-1␤ was released after the infection of monocytes with the less virulent M. avium (16). Similarly, infection of human monocytes or macrophages with virulent M. avium downregulated the production of proinflammatory cytokines (IL-1␤, TNF-␣, IL-6, and granulocyte-macrophage colony-stimulating factor) compared to that by cells infected with the less virulent strain (32). Studies with mice revealed that lipoarabinomannan derived from an attenuated strain of M. tuberculosis induced macrophage activation and TNF-␣ production, whereas lipoarabinomannan from the virulent Erdman strain was less stimulatory (2).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In both control and AIDS patients, more IL-1␤ was released after the infection of monocytes with the less virulent M. avium (16). Similarly, infection of human monocytes or macrophages with virulent M. avium downregulated the production of proinflammatory cytokines (IL-1␤, TNF-␣, IL-6, and granulocyte-macrophage colony-stimulating factor) compared to that by cells infected with the less virulent strain (32). Studies with mice revealed that lipoarabinomannan derived from an attenuated strain of M. tuberculosis induced macrophage activation and TNF-␣ production, whereas lipoarabinomannan from the virulent Erdman strain was less stimulatory (2).…”
Section: Discussionmentioning
confidence: 97%
“…It has been demonstrated that TNF-␣ plays an important role in the formation and maintenance of the granuloma and, along with IFN-␥, activates macrophages to produce effector molecules such as toxic oxygen and nitrogen intermediates (21). Interference with the production of appropriate mediators by lymphocytes and macrophages might be one of the pathogenic mechanisms employed by some mycobacteria (32).…”
mentioning
confidence: 99%
“…MAC has been reported to induce the production of certain cytokines, including interleukin-1, interleukin-6, tumor necrosis factor-alpha , granulocyte-monocyte colonystimulating factor, and granulocyte colony-stimulating factor (10)(11)(12)(13) (15). In the present case, the ratio was higher than 1 ( Table 1).…”
Section: Tion Of M Intracellulare On the First Admission Confirmed Tmentioning
confidence: 99%
“…18 reported that SmT and SmD variants induced a differential release of IL-1 a, IL-lp and IL-6 from nornial human monocytes and suggested that disturbances of cytokine production could contribute to MAC survival within cells, and then establish the infection. The aim of this study was to examine the production of cytokines from SmD-or SmT-infected monocytederived human macrophages, for a more complete evaluation of the release of these immunoregulatory proteins following MAC stimulation.…”
Section: Introductionmentioning
confidence: 99%